2017
DOI: 10.1002/2016ja023380
|View full text |Cite
|
Sign up to set email alerts
|

Creating space plasma from the ground

Abstract: We have performed an experiment to compare as directly as realizable the ionization production rate by HF radio wave energy versus by solar EUV. We take advantage of the commonality that ionization production by both ground‐based high‐power HF radio waves and by solar EUV is driven by primary and secondary suprathermal electrons near and above ~20 eV. Incoherent scatter radar (ISR) plasma‐line amplitudes are used as a measure of suprathermal electron fluxes for ISR wavelengths near those for 430 MHz and are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 76 publications
2
16
0
1
Order By: Relevance
“…A generation of very intense radio-induced optical emission in red and green lines with a high ratio of green to red line of 0.35-0.5 in the course of the X-mode pump pulses was found by Blagoveshchenskaya et al (2014). Carlson and Mantas (1982) and Carlson et al (2016) have found that the flux of accelerated electrons can produce an increased production of ionization. The EISCAT UHF radar observations clearly demonstrated that electron density enhancements by 50-70% from the background level were observed above the reflection height of a pump wave in a wide altitude content (up to about 600 km) in all X-mode HF heating experiments not depending on the excitation of HF-induced Langmuir and ion-acoustic plasma waves.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…A generation of very intense radio-induced optical emission in red and green lines with a high ratio of green to red line of 0.35-0.5 in the course of the X-mode pump pulses was found by Blagoveshchenskaya et al (2014). Carlson and Mantas (1982) and Carlson et al (2016) have found that the flux of accelerated electrons can produce an increased production of ionization. The EISCAT UHF radar observations clearly demonstrated that electron density enhancements by 50-70% from the background level were observed above the reflection height of a pump wave in a wide altitude content (up to about 600 km) in all X-mode HF heating experiments not depending on the excitation of HF-induced Langmuir and ion-acoustic plasma waves.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…Wuhan (30.4 • N, 114.0 • E), which is typical mid-latitude, is selected as the location of the heating transmitter. The magnetic dip of Wuhan is 45 • , which is nearly identical to that of Arecibo (Carlson et al, 2016). Figure 1 shows the initial ionospheric electron density and temperature profile at 00:00 LT adopted from the international reference ionosphere model (IRI-2012) (Bilitza et al, 2011).…”
Section: Ionospheric Background and Simulation Parametermentioning
confidence: 89%
“…The scientific concerns of ionospheric heating include a large range of plasma physics topics involving Ohmic/Joule heating, parametric instability, particle acceleration, Langmuir turbulence, VLF/ELF/ULF wave generation, etc. (Foster et al, 1983;Wong et al, 1971;Ungstrup et al, 1979;DuBois et al, 1990;Brinca et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Today there are four active HF facilities around the world. They are: SURA in Russia [Belikovich et al, 2007], EISCAT heating facility (built and formerly operated by Germany's Max-Planck Institute) in Norway [Rietveld et al, 2016], HAARP in Alaska, USA [Pedersen and Carlson, 2001], and most recently a new HF facility for the Arecibo 300 m antenna [Carlson et al, 2017]. Only Arecibo and the EISCAT HF facilities are co-located with incoherent scatter radars (ISRs), although HAARP has a small UHF phased array radar called the Modular UHF Ionospheric Radar (MUIR) which can receive HF-enhanced echoes normally seen with ISRs.…”
Section: Ground Facilitiesmentioning
confidence: 99%